Answer:
the answer would be 72
Step-by-step explanation:
Answer:
Step-by-step explanation:
y = 3x -6
x = -2, y = -12
x = -1, y = -9
x = 0, y = -6
x = 1, y = -3
x = 2, y = 0
x= 3, y = 3
x -2 -1 0 1 2 3
y -12 -9 -6 -3 0 3
Answer:
Trapezoid 1 (left side):
Base 1 = 2
Base 2 = 5
Trapezoid 2 (right side):
Base 1 = 6
Base 2 = 8
Step-by-step explanation:
<u>1st trapezoid:</u>
b_1 = x
b_2 = x + 3
h = 4
Hence, area (from formula) would be:
![A=\frac{h}{2}(b_1+b_2)\\A=\frac{4}{2}(x+x+3)\\A=2(2x+3)\\A=4x+6](https://tex.z-dn.net/?f=A%3D%5Cfrac%7Bh%7D%7B2%7D%28b_1%2Bb_2%29%5C%5CA%3D%5Cfrac%7B4%7D%7B2%7D%28x%2Bx%2B3%29%5C%5CA%3D2%282x%2B3%29%5C%5CA%3D4x%2B6)
<u>2nd trapezoid:</u>
b_1 = 3x
b_2 = 4x
h = 2
Putting into formula, we get:
![A=\frac{h}{2}(b_1+b_2)\\A=\frac{2}{2}(3x+4x)\\A=1(7x)\\A=7x](https://tex.z-dn.net/?f=A%3D%5Cfrac%7Bh%7D%7B2%7D%28b_1%2Bb_2%29%5C%5CA%3D%5Cfrac%7B2%7D%7B2%7D%283x%2B4x%29%5C%5CA%3D1%287x%29%5C%5CA%3D7x)
Let's equate both equations for area and find x first:
![4x+6=7x\\6=7x-4x\\6=3x\\x=\frac{6}{3}\\x=2](https://tex.z-dn.net/?f=4x%2B6%3D7x%5C%5C6%3D7x-4x%5C%5C6%3D3x%5C%5Cx%3D%5Cfrac%7B6%7D%7B3%7D%5C%5Cx%3D2)
We can plug in 2 into x and find length of each base of each trapezoid.
Trapezoid 1 (left side):
Base 1 = x = 2
Base 2 = x + 3 = 2 + 3 = 5
Trapezoid 2 (right side):
Base 1 = 3x = 3(2) = 6
Base 2 = 4x = 4(2) = 8